2017
DOI: 10.1038/srep42666
|View full text |Cite|
|
Sign up to set email alerts
|

Laser-Driven Ion Acceleration from Plasma Micro-Channel Targets

Abstract: Efficient energy boost of the laser-accelerated ions is critical for their applications in biomedical and hadron research. Achiev-able energies continue to rise, with currently highest energies, allowing access to medical therapy energy windows. Here, a new regime of simultaneous acceleration of ~100 MeV protons and multi-100 MeV carbon-ions from plasma micro-channel targets is proposed by using a ~1020 W/cm2 modest intensity laser pulse. It is found that two trains of overdense electron bunches are dragged ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 51 publications
3
54
0
Order By: Relevance
“…For given r 0 and σ 0 , η is determined by a 0 . Both the radial electron momentum p r and the longitudinal electron momentum p x from the high-ordermode electric field E x are proportional to a 0 [5]. For the contribution of the laser ponderomotive force to p x , the superluminous phase velocity of the wave in the plasma waveguide must be taken into account if a 0 >a cr , where = -…”
Section: Simulation and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…For given r 0 and σ 0 , η is determined by a 0 . Both the radial electron momentum p r and the longitudinal electron momentum p x from the high-ordermode electric field E x are proportional to a 0 [5]. For the contribution of the laser ponderomotive force to p x , the superluminous phase velocity of the wave in the plasma waveguide must be taken into account if a 0 >a cr , where = -…”
Section: Simulation and Discussionmentioning
confidence: 99%
“…c v c 2 cr ph 1 2 is the critical amplitude and v ph is the light phase velocity [5]. In fact, it changes from as a 0 is further increased.In addition, we found that the density of the pulled-out wall electrons scales as c a 0 , where χ is related to the ionization degree of the wall material [5]. Therefore a 0 is closely related to η and therefore can affect the energy conversion efficiency from the laser to the TM modes.…”
Section: Simulation and Discussionmentioning
confidence: 99%
See 3 more Smart Citations